2022
DOI: 10.3389/fpls.2022.833682
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Nudix Hydrolase 1 Is Involved in Geranyl β-Primeveroside Production in Tea

Abstract: Geraniol is a potent tea odorant and exists mainly as geranyl glycoside in Camellia sinensis. Understanding the mechanisms of geraniol biosynthesis at molecular levels in tea plants is of great importance for practical improvement of tea aroma. In this study, geraniol and its glycosides from tea plants were examined using liquid chromatography coupled with mass spectrometry. Two candidate geraniol synthase (GES) genes (CsTPS) and two Nudix hydrolase genes (CsNUDX1-cyto and CsNUDX1-chlo) from the tea genome wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Additionally, bifunctional cytosolic mono-/sesquiterpene synthases have been identified, capable of producing monoterpenes (Aharoni et al ., 2004; Nagegowda et al ., 2008; Davidovich-Rikanati et al ., 2008). Further, in recent years an unexpected enzyme belonging to a NUDX hydrolase was shown to be involved in formation of monoterpene geraniol in the cytosol (Magnard et al ., 2015; Bergman et al ., 2021a; Zhou et al ., 2022). These studies indicated the contrasting evolution of monoterpene biosynthesis in different plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bifunctional cytosolic mono-/sesquiterpene synthases have been identified, capable of producing monoterpenes (Aharoni et al ., 2004; Nagegowda et al ., 2008; Davidovich-Rikanati et al ., 2008). Further, in recent years an unexpected enzyme belonging to a NUDX hydrolase was shown to be involved in formation of monoterpene geraniol in the cytosol (Magnard et al ., 2015; Bergman et al ., 2021a; Zhou et al ., 2022). These studies indicated the contrasting evolution of monoterpene biosynthesis in different plant species.…”
Section: Discussionmentioning
confidence: 99%